Laser Diode Pulse Driver - Francisco João Cunha Dias (2019)
A laser is a device that emits light through a process of optical amplification based on the stimulated emission of electromagnetic radiation. It can have many applications in different fields like communications systems, sensorization equipment, marking and cutting of materials, 3D printing, and many others. The Laser converts electrical power into optical power, and it is the aim of this project to study pulse modulation techniques, test existing pulse drivers and propose and design electronics for a pulse driver. It's important to understand how Lasers work, their characteristics and limitations, as well as different technics and different concepts of drivers. Another challenge proposed by the company was to use free software for the design and simulation of circuits as well as for the design of the PCB, being the gEDA tools for the schematic and the PCB and Ngspice for the simulation.